PENGUNGKAPAN MAKNA IMPERATIF DALAM KOMUNIKASI JUAL BELI - Izhar Izhar (Jurnal Pesona, 2015)
Abstract The speech form that communicates imperatively is not only interpreted as command utterances, but also has other meanings of imperative. Especially when a speech communicates indirectly, certainly need to know the hidden imperative. This study illustrates how important to understand the meaning of imperative that contains in various communications, including trading communications in order to obtain the purpose of communication straightly. This study uses qualitative approach with descriptive methods. The data was analyzed in depth and then presented straightly. The data of this study is the seller / buyer utterances in Pasarbaru Kedondong Pesawaran District of Lampung Province. The result of this study showed that imperative meaning of contradiction, requests, and suggestions always used in communication and selling.   Key Words: Imperative, Declarative, Interrogative, Context of Situation.